Stable Deep Doping of Vapor‐Phase Polymerized Poly(3, 4‐ethylenedioxythiophene)/Ionic Liquid Supercapacitors. Issue 16 (21st June 2016) - Karlsson, Christoffer; Nicholas, James; Evans, Drew; Forsyth, Maria; Strømme, Maria; Sjödin, Martin; Howlett, Patrick C.; Pozo‐Gonzalo, Cristina
Abstract: Liquid‐solution polymerization and vapor‐phase polymerization (VPP) have been used to manufacture a series of chloride‐ and tosylate‐doped poly(3, 4‐ethylenedioxythiophene) (PEDOT) carbon paper electrodes. The electrochemistry, specific capacitance, and specific charge were determined for single electrodes in 1‐ethyl‐3‐methylimidazolium dicyanamide (emim dca) ionic liquid electrolyte. VPP‐PEDOT exhibits outstanding properties with a specific capacitance higher than 300 F g −1, the highest value reported for a PEDOT‐based conducting polymer, and doping levels as high as 0.7 charges per monomer were achieved. Furthermore, symmetric PEDOT supercapacitor cells with the emim dca electrolyte exhibited a high specific capacitance (76.4 F g −1 ) and high specific energy (19.8 Wh kg −1 ). A Ragone plot shows that the VPP‐PEDOT cells combine the high specific power of conventional ("pure") capacitors with the high specific energy of batteries, a highly sought‐after target for energy storage. Abstract : Vapor trail : Vapor‐phase polymerized poly(3, 4‐ethylenedioxythiophene) (PEDOT) supercapacitor cells that employ 1‐ethyl‐3‐methylimidazolium dicyanamide as the electrolyte exhibit an outstanding performance with a specific cell capacitance of 76.4 F g −1 and a specific cell energy of 19.8 Wh kg −1 . PEDOT is stable at a high doping level of 0.7 under these conditions. This is a significant improvement compared with PEDOT synthesized from liquid solution and other common electrolytes.